If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5y = 12x + 2y Solving 3x + 5y = 12x + 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 3x + -12x + 5y = 12x + -12x + 2y Combine like terms: 3x + -12x = -9x -9x + 5y = 12x + -12x + 2y Combine like terms: 12x + -12x = 0 -9x + 5y = 0 + 2y -9x + 5y = 2y Add '-5y' to each side of the equation. -9x + 5y + -5y = 2y + -5y Combine like terms: 5y + -5y = 0 -9x + 0 = 2y + -5y -9x = 2y + -5y Combine like terms: 2y + -5y = -3y -9x = -3y Divide each side by '-9'. x = 0.3333333333y Simplifying x = 0.3333333333y
| 7a^2-38a+15=0 | | x^9/4 | | N=-0.095x^2+1.74x+60 | | 5x^3-5=3660 | | 7(9+x)=147 | | 5-8b+6-2b= | | 15x+40=8x-9 | | -33=-x+7x-3 | | h=6t^2+112t+1248 | | -2y^2+16y-x-28=0 | | -2(8t^2-48t-8)=0 | | X^3+4x=80 | | 47.75=5(2.95+x) | | 3(2x+5)-x=-5x-15 | | 3x=27.9 | | 4a^2-7a-2=0 | | x+(4x)=5 | | (2t^2-t-15)/(3t^2-8t-3) | | 3(2x+5)-x=4x+15 | | 6m^2=13m+38 | | =5+7(0)+4 | | ln(x)=1/9 | | y=-4/3x^2-8x | | -3x-23=3x+19 | | 7-4x-6x=-3 | | 2x+(1-x)=7 | | x+(x+1.3)+(x-1.3)=27.9 | | 3(2x+5)-x=15x+5 | | 225=50t | | x-1(x+7)=500 | | 1+4=2+3 | | 6m^2-5m-6=0 |